Hepatic Vein and Inferior Vena Cava Reconstruction during Hepatic Surgery Resection for Cancer (Journal of Renal and Hepatic Disorders, 2021)
Invasion of tumor in the liver requires surgical interventions that may reduce the effects or may eliminate the tumor-affected cells. The renewal of the hepatic vein and inferior vena cava has enabled most specialized oncologists and medical specialists to use advanced diagnostic methods in the treatment of the liver tumors. Liver resection has prolonged the lives of many patients and the invention of live donor organ transplants has effectively enabled the use of liver resection in most cancer centers across the world. By reviewing data from 10 articles, 21 surgical analyses were investigated and analyzed for the risks involved in the applications of reconstructions of hepatic vein and inferior vena cava in the surgical liver resection. The postoperative complications and the indications of reconstructions were mentioned. The results indicated that with these surgical procedures, complications are still involved but may be successful for particular patients.
Keywords: cancer/tumor; hepatic surgery; hepatic vein; inferior vena cava; liver resection; reconstruction